Genome-wide identification of the NAC family in Hemerocallis citrina and functional analysis of HcNAC35 in response to abiotic stress in watermelon - Cao, Lihong; Wang, Jinyao; Ren, Sijia; Jia, Yumei; Liu, Yue; Yang, Shanjie; Yu, Junshen; Guo, Xinjuan; Hou, Xiaojie; Xu, Jin; Li, Sen; Xing, Guoming (Frontiers in Plant Science, 2024)
NAC (NAM, ATAF, and CUC) transcription factor family, one of the important switches of transcription networks in plants, functions in plant growth, development, and stress resistance. Night lily (Hemerocallis citrina) is an important horticultural perennial monocot plant which has edible, medicinal, and ornamental values. However, the NAC gene family of night lily has not yet been analyzed systematically to date. Here, a total of 113 HcNAC members, which were unevenly distributed on 11 chromosomes, were identified and characterized from the Hemerocallis citrina genome. Phylogenetic analysis showed they could be categorized into 16 instinct subgroups. Proteins clustering together exhibited similar conserved motifs and intron-exon structures. Collinearity analysis indicated that segmental and tandem duplication might contribute to the great expansion of the NAC gene family in night lily, whose relationship was closer with rice than Arabidopsis.Additionally, tissue-specific pattern analysis indicated that most HcNAC genes had relatively higher expression abundances in roots. RNA-Seq along with RT-qPCR results jointly showed HcNAC genes expressed differently under drought and salinity stresses. Interestingly, HcNAC35 was overexpressed in watermelon, and the stress resilience of transgenic lines was much higher than that of wild-type watermelon, which revealed its wide participation in abiotic stress response. Our findings provide a new prospect for investigating the biological roles of NAC genes in night lily.